Isolasi Dan Karakterisasi Bakteri Termofilik Dari Oil Sludge Asal Kalimantan Timur - Mulya Fitrah Juniawan; Dita Artanti; Yuni Gayatri; AINUTAJRIANI AINUTAJRIANI (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2023)
Oil sludge is a product of petroleum mining activities and causes environmental pollution. However, oil sludge, including hazardous and toxic waste materials (B3), has been less effective in reducing oil sludge pollution. Thus, the researcher solved the issue by using hydrocarbonoclastic. It is necessary to use hydrocarbonoclastic bacteria isolated directly from their habitat (indigenous bacteria) as hydrocarbon degrading agents. Therefore, this study aimed to isolate and identify indigenous thermophilic bacteria from East Kalimantan Oil sludge. This study is an observational study that is analyzed descriptively. Procedure for isolation and identification of thermophilic bacteria from oil sludge grow on Synthetic Mineral Water media (SMW) with and without an autoclave. The Microbact Identification System Kit GNB 24E was used to characterize colonies macroscopically, microscopically, Gram staining, physiological tests (catalase, coagulase, and motility tests), and biochemically. The bacteria that were successfully isolated were later identified with Microbact Software and Bergey's book Manual of Determinative Bacteriology Ninth Edition. The results of the isolation and identification of thermophilic Indigenous bacteria from Oil Sludge Kalimantan Timur found Pseudomonas aeruginosa species with a similarity accuracy of 98.33%. The identified bacterial isolates can later be used as bioremediation agents on soils polluted with oil sludge.Â Keywords : Indigenous bacteria, Oil Sludge, Pseudomonas aeruginosa.